Tughlaq and the Stolen Sweets - Natasha Sharma (India Penguin Random House India, 2022)
Muhammad bin Tughlaq, the Sultan of Dihli, is outraged. Someone has stolen his favourite dessert, the sugared melons from Khurasim. What's worse, people are questioning his plans of torture and punishment. Who can help the Sultan solve this mystery?
Keywords: Historical Fiction -- Historical Fiction